2021
DOI: 10.1016/j.compbiomed.2021.104464
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of the bioflavonoids with five SARS-CoV-2 proteins targets: An in silico study

Abstract: Flavonoids have been shown to have antioxidant, anti-inflammatory, anti-proliferative, antibacterial and antiviral efficacy. Therefore, in this study, we choose 85 flavonoid compounds and screened them to determine their in-silico interaction with protein targets crucial for SARS-CoV-2 infection. The five important targets chosen were the main protease (Mpro), Spike receptor binding domain (Spike-RBD), RNA - dependent RNA polymerase (RdRp or Nsp12), non-structural protein 15 (Nsp15) of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“… 24 There was only marginal overlap between our enzymatic screening of flavonoid Mpro inhibitors and previous in silico screens. 22 Conversely, screens of small collections of flavonoids 43 , 44 or extracts of natural products 45 , 46 are far less inclusive and lack the extensive opportunity for SARs provided by enzymatic screening of a large flavonoid library. The finding that biflavones and galloylated flavonoids are enriched in Mpro inhibitors could help guide future identification and development of flavonoid-based treatments for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… 24 There was only marginal overlap between our enzymatic screening of flavonoid Mpro inhibitors and previous in silico screens. 22 Conversely, screens of small collections of flavonoids 43 , 44 or extracts of natural products 45 , 46 are far less inclusive and lack the extensive opportunity for SARs provided by enzymatic screening of a large flavonoid library. The finding that biflavones and galloylated flavonoids are enriched in Mpro inhibitors could help guide future identification and development of flavonoid-based treatments for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Endoribonuclease (EndoU or NSP15) is a 346 residue protein with three domains namely, the N-terminal domain, middle domain, and the C-terminal domain. The N-terminal domain was found to be responsible for the formation of a hexamer, while the C-terminal domain contains the active site of the protein that facilitates replication and processing of sub-genomic RNAs 9 12 . It was found that NSP15 hydrolyzes the phosphodiester bond that is located at the uridine (U) sites of single and double-stranded RNA molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of the binding power of the aforementioned compounds to the SARS-CoV-2 enzyme protease (6LU7) was conducted through the utilization of molecular docking strategy [ 39 , 40 ]. The generation of the three-dimensional models of the title compounds was done utilizing the builder user interface of MOE [ 41 ].…”
Section: Methodsmentioning
confidence: 99%